Need of carbon negative construction materials to sequester GHG and Global warming. - Vineet.V.Bodhe (Zenodo, 2021)
– Concrete is the key element for construction of buildings after its introduction in construction industry, it was supposed to be a gift for construction industry but its excessive use has become a threat with the amount of CO2 emitted each year during its production. Concrete contributes to green house gas emission and its production alone contributes to 102 mega tones of global CO2 production. Advancement in construction technologies like Tunnel formwork and Aluminium formwork has bought significant changes over conventional construction process. These technologies and advancement have replaced all the building elements with concrete, which eventually will result in growing demand for concrete production and CO2 emitted along with it. Before introduction of concrete, load bearing structures were built with masonry width 450mm and above but after its introduction only frame structure of the building were built in concrete except facade and internal walls, which were built with mud bricks, but in later stage with such an advancement in construction trends and technologies all the components of buildings are built in concrete including external and internal walls. If all the components of buildings are made in concrete, it will ultimately lead to excess concrete production and thus emitting maximum green house gas which will reflect in rising global temperature thus causing sea level rise up due to conversion of ice glaciers into water. This research paper emphasis on using carbon negative building blocks i.e Hempcrete blocks to absorb carbon from the atmosphere thus decreasing the global temperature and to have control over the disasters caused such as floods due to rising sea level. To mitigate ever increasing green house gases, use of sustainable material which is carbon negative is mandatory for building low rise as well as high rise towers. Carbon absorbing bio composite material which is hempcrete is advised to be used to sequester existing CO2 from the environment. : {"references": ["[1] Carbon clean , (2021). https://www.carbonclean.com/blog/reducing-cement-emissionswith-ccus-technologyco2", "[2] bbc.com/news/world-Europe-5785889, 57858826.", "[3] bbc.com/news/world-asia-india-57938839, china-57861067.", "[4] Dangendorf, S. et al. Reassessment of 20th century global mean sea level rise. Proc. Natl Acad. Sci. 114, 5946\u20135951 (2017).", "[5] IEA, 2020, Energy Technology Perspectives 2020. https://www.iea.org/reports/energy-technologyperspectives-2020", "[6] Kopp, R. E. et al. Probabilistic 21st and 22nd century sea-level projections at a global network of tide-gauge sites. Earth's. Future 2, 383\u2013406 (2014).", "[7] Huss et al, [2017]", "[8] Arnaud & Gourlay, (2011) \"Experimental study of parameters influencing mechanical properties of hemp concrete\".pp- 51-55.", "[9] Hauer, M. E. Migration induced by sea-level rise could reshape the US population landscape. Nat. Clim. Change 7, 321\u2013325 (2017).", "[10] Edwards, T. L. et al. Revisiting Antarctic ice loss due to marine ice-cliff instability. Nature 566, 58 \u201364 (2019).", "[11] Gesch, D. B. Best Practices for Elevation-Based Assessments of Sea-Level Rise and Coastal Flooding Exposure. Front. Earth Sci. 6 (2018).", "[12] Vafeidis, A. T. et al. Water-level attenuation in global-scale assessments of exposure to coastal flooding: a sensitivity analysis. Nat. Hazards Earth Syst. Sci. 19, 973\u2013984 (2019).", "[13] Rebecca Lindsey(2021) Climate change : Global sea level.Climate.org [onlinehttps://www.climate.gov/newsfeatures/understanding-climate/climate-change-global-sea-level] Accessed June 2021.", "[14] source[https://www.nasa.gov/specials/sea-level-rise2020/]Accessed june 2021.", "[15] M. Garside (Feb 17, 2021) Major countries in world wide cement production 2010 to 2020. Statista.com [https://www.statista.com/statistics/267364/world-cementproduction-by-country/] Accessed May 2021.", "[16] GCCA GNR Database [https://gccassociation.org/sustainability-innovation/gnr-gcca-innumbers/].", "[17] Picandet V. (2017), \"Bulk Density and Compressibility\", In: Amziane S., Collet F. ed., Bioaggregates Based Building Materials, RILEM State-of-the-art Reports 23, Springer, pp. 111124.", "[18] Piot A., B\u00e9jat T., Jay A., Bessette L., Wurtz E. and BarnesDavin L. (2017) \"Study of a hempcrete wall exposed to outdoor climate: Effects of the coating\", Construction and Building Materials, 139 pp.540-550.", "[19] Jami T., Rawtani D. and Agrawal Y.K. (2016), \"Hemp concrete: carbon-negative construction\", Emerging Materials Research, 5(2), pp. 240-247", "[20] Mohammad Mehdi ,Jalili, Seyyed Yahya Mousavi, Amir Soheil Pirayeshfar. (2014), Investigating the acoustical properties of carbon fiber-, glass fiber-, and hemp fiber-reinforced polyester composites.", "[21] World weather attribition (2021) https://www.worldweatherattribution.org/western-north-americanextreme-heat-virtually-impossible-without-human-caused-climatechange/ Accessed \u2013 July 2021", "[22] Jami T., (2016), \"A Study on Carbon Sequestration of Lime Hemp Concrete\", Gujarat, India."]}